Evaluation of physical workload standards and guidelines from a Nordic perspective - Fallentin, Nils; Viikari-Juntura, Eira; Wærsted, Morten; Kilbom, Åsa (Scandinavian Journal of Work, Environment & Health, 2001)
In 1997 the Nordic Council of Ministers decided to initiate a project with the aim of evaluating existing physical workload standards from a Nordic perspective as a background for possible future initiatives and needs. The decision reflects Nordic interest in critically validating the rapidly increasing number of European and American standards and guidelines being developed for physical workload. A working group was appointed consisting of representatives of the Danish, Finnish, Norwegian, and Swedish institutes of occupational health. This report presents the results of the group`s considerations and its main conclusions. In general, the project aimed at providing a thorough review of the different standards, a description of their legal status, and a judgment of their scientific and practical value. Following a brief account of the history of physical workload standards and a theoretical account of the problems involved, 26 standards or guidelines are grouped and reviewed in the following seven categories: (i) general ergonomics standards, (ii) guidelines for manual materials handling, (iii) guidelines for repetition, force, and posture in monotonous, repetitive work, (iv) vibration standards, (v) guidelines for energy consumption, (vi) guidelines for specific industries, and (vii) acute overload guidelines. The standards and guidelines represent a variety of issuing bodies and organizations, for example, the European Committee for Standardization (CEN), the International Organization for Standardization (ISO), the American National Standards Institute (ANSI), the International Ergonomics Association (IEA), the (United States) National Institute for Occupational Safety and Health (NIOSH), and the (United States) Occupational Safety and Health Administration (OSHA).As a means of promoting a "code of practice" for the evaluation of physical workload standards, a framework of criteria for identifying scientifically "good" and practically efficient standards was established, and the following three key areas were identified in the evaluation procedure: (i) scientific coherency, (ii) effectiveness, and (iii) usability. [Scientific coherency considers the degree to which standards are related to scientific knowledge on the causes of the injuries or diseases in question. The effectiveness of an occupational safety and health standard describes the impact of the standard with regard to the prevention of occupational disease and injury. And the usability criterion evaluates the potential for implementing the standard.] Prior to the evaluation, the standards were divided into the following two groups according to their level of accuracy: (i) standards presenting quantitative guidelines for specific exposures with precise and numerical acceptance criteria and (ii) process-type standards presenting mainly qualitative guidelines and focusing on a program approach. The two groups were evaluated separately, and the results have been presented in two different sections. In general the evaluation was the most favorable for process-type standards. The most conspicuous difference between process-type and quantitative-type standards was found for the "scientific coherency" criteria. The quantitative standards involve the dilemma of conflict between the intention of providing numerical acceptance criteria differentiating between hazardous and safe jobs and the paucity of scientifically well-founded data allowing such quantitative risk estimates to be established. To solve this problem as optimally as possible, better designed epidemiologic studies using good exposure and outcome assessment methods are needed. The report provides some support for the view that regulatory actions against work-related musculoskeletal disorders will be the most successful if an integrated ergonomic program approach is adapted. A substantial number of case studies indicates that ergonomic programs can be efficient in protecting workers against work-related musculoskeletal disorders. The General Accounting Office (GAO) study of several companies with ergonomic programs in the United States gives strong - although indirect - support for the belief that well-managed ergonomic programs with high commitment on the part of stakeholders can be efficient. In general, however, knowledge or documentation on the effectiveness of legislation or standards in reducing work-related musculoskeletal disorders is limited. The need for the development of the instruments required for a thorough survey and evaluation of the effectiveness of the regulatory actions is thus obvious. In Europe the Trade Unions Technical Bureau for Health and Safety (TUTB) has initiated several projects to monitor the transposition and application of European health-at-work directives, and these attempts should be encouraged. At the same time, the potential benefits of quantitative guidelines or numerical threshold limit values remain to be proved. Despite remarkable efforts made by a large number of individual researchers and scientists involved in the process of standardization—and some promising elements in, for example, the new Sashington State ergonomics rule—too many quantitative guidelines are still inconsistent and have limited scientific credibility. The unfavorable rating for the majority of quantitative standards should not be interpreted as an argument against giving practical recommendations and quantitative suggestions. It should be recognized that quantitative guidelines identifying jobs at extreme high (or low) risk may be appropriate and useful in some cases. The limited amount of epidemiologic evidence calls, however, for concern when such recommendations are presented as "safe" thresholds capable of eliminating the risk of health impairment to workers. The report emphasizes that efforts are needed to improve the usability and "user friendliness" of future guidelines and enhance the process of implementation through the involvement of labor market partners. The incorporation of workplace experience in the process of standard making is essential and the organized, systematized feedback of users` experience in the revision of existing standards should be given high priority. In the Nordic countries, the use of regulatory actions in the prevention of musculoskeletal disorders is based on identical principles with strong adherence to the common European rules on safety and health at work established in the directives of the European Union (EU). The EU framework directive (89/391/EEC) and its individual directives have been implemented in national law in all the Nordic countries with only minor amendments to the minimum requirements set at the European level. This project found that the combination of adapting the process-oriented EU directives and the use of nonmandatory, mainly qualitative guidelines and provisions constitutes a consistent and sound approach to regulatory action. The nonmandatory guidelines frequently represent a valuable compromise. They have been successful in covering many aspects of risk assessment and have avoided unsupported quantitative recommendations without appearing diluted.A future challenge to this consistent approach may, however, be the voluntary technical standards that are being developed to give new products a presumption of conformity with the CEN machine directive. A series of draft CEN standards - addressing aspects directly related to musculoskeletal disorders and presenting highly quantitative recommendations - is presently in a stage of public hearing. If adopted, these CEN standards will be national standards in all the Nordic countries. Although the CEN standards are subordinate to national labor market regulation, a potential problem relates to the confusion of having two sets of standards covering the same musculoskeletal risk factors with an entirely different approach and paradigm. Currently this problem has not been recognized in the Nordic countries. The present report recommends that a debate on the pros and cons of introducing such an element of confusion into national work environment policies be initiated and completed before the voting procedure is terminated for the draft standards. A final aspect in the implementation issue concerns the legislative framework of the European Union. The fact that EU legislation on safety and health at work forms the basis for regulatory actions in all the Nordic countries emphasizes the obligations placed on the Nordic countries to promote initiatives to improve this framework. There is a need for new regulation at the community level, and also stock should be taken of existing directives, the most pertinent problem in this respect being the need to add to the number of individual directives within the realm of the framework directive. A directive on monotonous and repetitive work to supplement the manual handling directive could be an important and appropriate new initiative. A repetitive work directive would be potentially beneficial for all EU member states and would, at the same time, transfer momentum to preventive efforts in the Nordic countries.
Keywords: acute overload; aged; back injury; carrying; Denmark; energy consumption; energy expenditure; environmental disease process; ergonomic program management; ergonomic standards; ergonomics program; ergonomics requirements; ergonomics rule; evaluation; evaluation criterion; exposure assessment; fall injury; Finland; force limits; guideline; guidelines for practitioners; hand-transmitted vibration; health requirements; historical perspective; human exposure; identification of risk factors; job design; lifting; machinery ergonomics; machinery operation; manual handling; manual lifting task; manual materials handling; maximal aerobic capacity; mechanical shock; mechanical vibration; monotonous work; MSD; musculoskeletal disorder; Nordic perspective; Norway; physical workload standard; posture; quantitative standard; reduction of exposure; repetition; repetitive motion injury; repetitive movement; repetitive work; risk exposure assessment; risk factor; safety requirement; shoulder complaint; slip injury; Sweden; threshold limit value; vibration; vibration standard; visual display unit; whole-body vibration; work posture; work-related cumulating trauma disorder; work-related musculoskeletal disorder; worker; workload